Acute Myelopathy as Initial Presentation of Disseminated Histoplasmosis: A Case Report - Lisle Blackbourn; Elisa Yoo; Michael D. Lunt; Umair Hamid (Case Reports in Infectious Diseases)
Histoplasmosis is a fungal infection caused by the fungus Histoplasma capsulatum that can rarely present with central nervous system (CNS) manifestations that include meningitis, encephalitis, focal brain or spinal cord lesions, and stroke syndromes. Because of this variation from patient to patient, CNS histoplasmosis is a difficult clinical diagnosis to make, which can be further hindered by no highly sensitive diagnostic testing available. Here, we present a unique case of a 46-year-old male immunocompromised due to type 1 diabetes mellitus with disseminated histoplasmosis as an acute presentation of myelopathy. Patient had left leg weakness for a few days prior to presentation and a neurological exam remarkable for signs of acute thoracic myelopathy, specifically concerning for Brown-Séquard syndrome. MRI imaging demonstrated an enhancing thoracic spinal cord lesion along with multiple cerebral enhancing lesions, bilateral adrenal masses, and innumerable pulmonary nodules. Biopsy results demonstrated yeast forms consistent with Histoplasma species.